Upaya guru PAI dalam menumbuhkan minat belajar sejarah kebudayaan Islam di SMP Muhammadiyah 8 Kebakkramat - Dewi Nurmita Sari; Hafidz Hafidz (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The purpose of this study was to describe the efforts made by PAI teachers in cultivating interest in learning the Islamic Cultural History subject for students at SMP Muhammadiyah 8 Kebakkramat. Then, this study also aims to identify what are the supporting factors and inhibiting factors towards the teacher's efforts to foster interest in learning the Islamic Cultural History subject for students at SMP Muhammadiyah 8 Kebakkramat. This research is a qualitative research using a phenomenological approach with data collection techniques, namely observation, interviews, and documentation. The data sources in this study were the principal, teachers, and students at SMP Muhammadiyah 8 Kebakkramat. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this study uses three types of triangulation, namely source triangulation, technical triangulation and time triangulation. The results of this study are the efforts made by PAI teachers to foster students' interest in learning in several ways, such as good classroom management, giving motivation, various learning methods, fun learning media, giving gifts and punishments, and providing evaluations. The supporting factors for the success of cultivating student interest in learning are the role of the school principal, the role of the Islamic Cultural History teacher, and the cooperation between teachers, parents, and students. Meanwhile, the inhibiting factors for the teacher's efforts to foster student interest include a lack of motivation in students, inadequate infrastructure, and an unsupportive social environment. technique triangulation and time triangulation. The results of this study are the efforts made by PAI teachers to foster students' interest in learning in several ways, such as good classroom management, giving motivation, various learning methods, fun learning media, giving gifts and punishments, and providing evaluations. The supporting factors for the success of cultivating student interest in learning are the role of the school principal, the role of the Islamic Cultural History teacher, and the cooperation between teachers, parents, and students. Meanwhile, the inhibiting factors for the teacher's efforts to foster student interest include a lack of motivation in students, inadequate infrastructure, and an unsupportive social environment. technique triangulation and time triangulation. The results of this study are the efforts made by PAI teachers to foster students' interest in learning in several ways, such as good classroom management, giving motivation, various learning methods, fun learning media, giving gifts and punishments, and providing evaluations. The supporting factors for the success of cultivating student interest in learning are the role of the school principal, the role of the Islamic Cultural History teacher, and the cooperation between teachers, parents, and students. While the inhibiting factors for the teacher's efforts to foster student interest such as lack of motivation in students, inadequate infrastructure, and an unsupportive social environment.